Total curvature and area of curves with cusps and of surface maps - Ekholm, Tobias; Kutzschebauch, Frank (MATHEMATICA SCANDINAVICA, 2005)
A curvature-area inequality for planar curves with cusps is derived. Using this inequality, the total (Lipschitz-Killing) curvature of a map with stable singularities of a closed surface into the plane is shown to be bounded below by the area of the map divided by the square of the radius of the smallest ball containing the image of the map. This latter result fills the gap in Santaló's proof of a similar estimate for surface maps into $R^n$, $n>2$.